Analisis Determinan Kepatuhan Wajib Pajak Kendaraan Bermotor di Kantor SAMSAT - Lestari, Desak Made Dian; Ngurah Agung Kresnandra, Anak Agung (E-Jurnal Akuntansi; Vol 33 No 6 (2023)DO - 10.24843/EJA.2023.v33.i06.p019, 2023)
The decline in realized revenues and the high arrears on motor vehicle taxes indicate a low level of taxpayer compliance. The study aims to determine the effect of income levels, understanding of tax regulations, and service quality on motor vehicle taxpayer compliance at the SAMSAT Office of Gianyar Regency. The sample used was 100 motor vehicle taxpayers. Purposive sampling was used as a sample determination method. The questionnaire method was used as a data collection method. Multiple linear regression analysis is the analytical technique used in this study. The results showed that the level of income, understanding of tax regulations, and quality of service had a positive effect on motor vehicle taxpayer compliance. This research provides empirical support for the Theory of Planned Behavior and attribution theory. Keywords: Income Levels; Understanding of Tax Regulations; Service Quality; Taxpayer Compliance